The education of women in the century - Bowen, May Haines (My University, 1896)
Introduction: In all that through years past has given us our art, science, and literature, woman has had her place. Deborah, a judge, Sappho a poet whose fame rivaled that of Homer, and Cleopatra, a woman learned in language and a ruler of one of the leading nations of her time, show that, before the Christian era, woman had won recognition in pursuits to which men in this advanced age, some forbid her entrance. In the fifth century Hypatia was a successful lawyer, mathematician, and philosopher. Caroline Herschel’s work in establishing the science of astronomy deserves an equal place with that of her brother William Botany and entomology owe much the patient and persistent work of Maria Elizabeth Humboldt.
Citation: Bowen, May Haines. The education of women in the century. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Art; Science; Literature; Woman; Education; Pursuits; Theses; Manuscripts (documents)